Clinical profile of cerebral venous sinus thrombosis and the role of imaging in its diagnosis in patients with presumed idiopathic intracranial hypertension - Agarwal, Prateek (Medknow Publications, 2010)
Retrospective descriptive study reporting the rate of occurrence of cerebral venous sinus thrombosis (CVST), highlighting the role of magnetic resonance imaging (MRI) and magnetic resonance venography (MRV) in patients with presumed idiopathic intracranial hypertension (IIH). Study was conducted in the department of neuro-ophthalmology at a tertiary eye care center in South India. Data from 331 patients diagnosed with IIH from June 2005 to September 2007 was included. Inclusion criteria were: Elevated opening cerebrospinal fluid (CSF) pressure of more than 200 mm of water on lumbar puncture, normal CSF biochemistry and microbiology, and normal neuroimaging as depicted by computed tomography(CT) scan. Exclusion criteria were: Space-occupying lesions, hydrocephalus, meningitis, intracranial pressure within normal range, abnormal CSF biochemistry and microbiology. The remaining patients were evaluated with MRI and MRV. CVST was present in 11.4% of patients who were presumed to have IIH (35/308). MRI alone identified 24 cases (68%) of CVST, while MRI used in combination with MRV revealed an additional 11 cases (32%). Risk factors associated with CVST were identified in nine out of 35 patients (26%). CVST may be misdiagnosed as IIH if prompt neuroimaging by MRI and MRV is not undertaken. Risk factors of CVST may not be apparent in all the cases and these patients are liable to be missed if CT scan alone is used for neuroimaging, hence MRI, combined with MRV should be undertaken to rule out CVST.